2014
DOI: 10.1186/1476-4598-13-126
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous deletion of the activin A receptor, type IB gene is associated with an aggressive cancer phenotype in pancreatic cancer

Abstract: BackgroundTransforming growth factor, beta (TGFB) signal is considered to be a tumor suppressive pathway based on the frequent genomic deletion of the SMAD4 gene in pancreatic cancer (PC); however; the role of the activin signal, which also belongs to the TGFB superfamily, remains largely unclear.Methods and resultsWe found a homozygous deletion of the activin A receptor, type IB (ACVR1B) gene in 2 out of 8 PC cell lines using array-comparative genomic hybridization, and the absence of ACVR1B mRNA and protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 34 publications
(54 reference statements)
3
21
0
Order By: Relevance
“…The mutations identified are similar to the well-characterized frameshift mutations in TGFBR2 [62]. Inactivation of ACVRIB so far has only been identified in pancreatic cancer as a consequence of a somatic mutation [63], and homologous deletion is associated with an aggressive phenotype in pancreatic cancer [64]. Based on the 120 esophageal squamous tumor tissues we analyzed in this study, we found that ACVRIB can also be lost in ESCC.…”
Section: Discussionsupporting
confidence: 60%
“…The mutations identified are similar to the well-characterized frameshift mutations in TGFBR2 [62]. Inactivation of ACVRIB so far has only been identified in pancreatic cancer as a consequence of a somatic mutation [63], and homologous deletion is associated with an aggressive phenotype in pancreatic cancer [64]. Based on the 120 esophageal squamous tumor tissues we analyzed in this study, we found that ACVRIB can also be lost in ESCC.…”
Section: Discussionsupporting
confidence: 60%
“…RNAseq data from TCGA showed a positive association of only tumour activin A expression on mortality and not for genes encoding Inhibin-alpha, follistatin and related proteins, activin B, or receptors ACVR1B, ACVR1C, ACVR2A, and ACVR2B (not shown), despite empirical evidence of certain of these receptors influencing tumour phenotype. [60][61][62][63] Moreover, RNA expression of the closely related proteins, myostatin, and GDF-11 in tumours was actually associated with reduced mortality, despite their ability to induce systemic wasting. 64,65 These results suggest highly context- specific roles of these factors in PDAC disease progression and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study has demonstrated that TGF- β /Smad signalling is operational in pancreatic cancer (Togashi et al , 2014). When TGF- β is activated, Smad2 is phosphorylated and undergoes dimerisation with Smad3, thus allowing its translocation into nucleus in cancer cells, promoting the EMT progress (Liu et al , 2012; Liu et al , 2015).…”
Section: Discussionmentioning
confidence: 99%